T92. HIPPOCAMPAL GRAY MATTER VOLUME IS ASSOCIATED WITH COGNITION, POSITIVE SYMPTOMS, AND DURATION OF UNTREATED PSYCHOSIS IN THE FIRST EPISODE SCHIZOPHRENIA SPECTRUM. (9th April 2019) - Curtis, Mark; Coffman, Brian; Salisbury, Dean
Abstract: Background: Hippocampal volumes are reduced in long-term and early schizophrenia. The hippocampus has an established role in working memory in healthy individuals, and less hippocampal volumes are associated with more severe symptoms in long-term schizophrenia. It remains unclear how hippocampal volumes relate to cognitive deficits, symptom severity, and illness duration early in schizophrenia. Therefore, we investigated relationships between hippocampal gray matter volume, cognitive performance, symptom severity, and duration of untreated psychosis (DUP) in first episode schizophrenia-spectrum individuals (FESz). Methods: T1-weighted MRI scans were acquired on 33 first-episode (FESz) and 32 matched healthy control (HC) individuals. Freesurfer was used to segment and estimate gray matter volumes in the left and right hippocampus. For group difference comparisons, volumes were normalized to total intracranial content. Cognitive ability was measured by the MATRICS Consensus Cognitive Battery (MCCB). DUP, measured in days, was calculated by taking the difference between the date of their first psychotic symptom and the date they either started antipsychotic medication or their assessment date. The log was taken of DUP to account for the skew of a few individuals with large DUP. Symptoms were rated with the Positive and Negative Syndrome Scale (PANSS). Spearman correlations were used to investigate these relationships. Results: There were no differences in hippocampal volumes between healthy controls and FESz. In healthy controls, left hippocampus was significantly correlated with composite MCCB (ρ=0.39, p=0.028), and right hippocampus volume was related to MCCB scores at trend level (ρ=0.32, p=0.079). Similarly, in FESz, both left (ρ=0.38, p=0.037) and right (ρ=0.36, p=0.049) hippocampus volumes correlated with composite MCCB scores. In FESz, both left (ρ=0.47, p=0.015) and right (ρ=.49, p=0.011) hippocampus volumes correlated positively with PANSS Positive scores. In addition, both the left (ρ=0.39, p=0.033) and right (ρ=0.39, p=0.036) hippocampus correlated positively with DUP. Discussion: In both HC and FESz, greater hippocampal gray matter volume was associated with better performance on a battery of cognitive tasks. In FESz, greater hippocampal volumes were associated with worse positive symptoms and a longer DUP. As these relationships appear paradoxical, it can be speculated that the individuals with greater hippocampal volumes have greater cognitive ability that potentially contributes to more elaborate and severe positive symptoms and greater resilience before needing first clinical contact. There were no group differences in volumes, but future studies following these individuals longitudinally will examine these relationships and whether hippocampal gray matter volume declines.